Behaviour, Attitudes and Opinion of Large Enterprise Employees with Regard to Their Energy Usage Habits and Adoption of Energy Saving Measures - Nisiforou, Olympia A.; Poullis, Sophocles; Charalambides, Alexandros G. (My University, 2012)
Occupants’ behaviour is one of the important aspects in diminishing energy waste. It is imperative that working environments should provide comfort to occupants and at the same time, they should also be in line with energy saving practices. The present study aims in investigating energy usage habits of a large enterprise employees in Cyprus, in evaluating their perception on consumption on various energy saving measures and finally, in statistically analyzing their behaviour, attitudes and opinion on energy usage and energy saving measures. Furthermore, the decisions taken by the upper management and its role on energy management is presented and analysed. To achieve the above aims, a detailed questionnaire was designed. Results showed that the majority of employees acknowledge that there is energy waste and that, in theory, they would be open to energy saving measures. They tend to believe that a complete energy management system must be applied, but when they were asked specifically about temperature control, they prefer individual control. Thus, they are not willing to sacrifice their own personal satisfaction for these measures. Furthermore, statistical analysis showed that employees sharing an office and have either less than 10 or more than 20 years of employment are the most dissatisfied about room temperature and thus, they would pose a difficulty in accepting energy saving measures. Finally, the upper management lacks in the promotion of energy saving measures, and this also contributes negatively in the employees’ behaviour.
Keywords: Behaviour; Energy consumption; Employees’ opinion; Large enterprises